RESPON PERTUMBUHAN DAN HASIL TANAMAN TELANG (Clitoria ternatea L.) DENGAN PEMBERIAN POC MULTIPLANT - Sundari; Erwin Arief Rochyat; Dimas Yulianto (Jurnal Magrobis, 2022)
This study aims to determine the effect of giving POC Multiplant on plant growth and yield of Telang (Clitoria ternatea L.). This research starts from April to May 2021, at Bukit Biru village, Tenggarong Sub District, Kutai Kartanegara District, East Kalimantan Privince. This research was arranged using a Randomized Complete Block Design (RCBD) with POC Multiplant (d) consistend of five levels namely : d0 (without POC Multiplant), d1 (5 cc/L water POC Multiplant), d2 (10 cc/L water POC Multiplant), d3 (15 cc/L water POC Multiplant) and d4 (20 cc/L water POC Multiplant). The result of research showed that the POC Multiplant treatment had no significant effect on all parameters, namely plant height, age of first flowering, and also the number of flowers. The highest yield of plants aged 7 days after planting was obtained from treatment d2 (10 cc/L water POC Multiplant) with an average of 27,60 cm and the lowest was from treatment d4 (20 cc/L water POC Multiplant) with an average of 24,50 cm. The highest yield of plants aged 14 days after planting was obtained from treatment d3 (15 cc/L water POC Multiplant) with an average of 63,80 cm and the lowest was from treatment d0 ( without POC Multiplant) with an average of 57,90 cm. While the highest yield of plants at harvest was obtained from treatment d1 (5 cc/L water POC Multiplant) with an average of 88,20 cm and the lowest at treatment do (without POC Multiplant) with an average of 75,30 cm. The fastest results of flowering age were obtained from treatment d1 (5 cc/L water POC Multiplant) with an average of 23,40 days and the longest with treatment d0 (without POC Multiplant) with an average of 23,90 days. The highest yield of interest was obtained in treatment d1 (5 cc/L water POC Multiplant) with an average of 12,60 flowers and the lowest in treatment d2 (10 cc/L water POC Multiplant) and d4 (20 cc/L water POC Multiplant) with an average of 10,08 flowers.